Brill's Companion to Euripides (2 vols) - Markantonatos, Andreas, (Brill's Companions to Classical Studies., 2020)
Brill's Companion to Euripides offers 49 specially commissioned essays from leading international scholars which give critical examinations of the progress and direction of numerous wide-ranging debates about various aspects of Euripidean drama. Each chapter, as well as covering a wide diversity of thematic angles, provides readers with an authoritative and state-of-the-art survey of current thinking and research in a particular subject area. Recent advances in scholarship have raised new questions about Euripides and Attic drama, and have overturned some long-standing assumptions and canons. Besides presenting a comprehensive and authoritative guide to understanding Euripides and his masterworks, this companion provides scholars and students with compelling fresh perspectives upon a broad range of issues in the rapidly evolving field of Euripidean studies.